Strategic Combination of Theory, Plain Language, and Trusted Messengers Contribute to COVID-19 Vaccine Uptake: Lessons Learned from Development and Dissemination of a Community Toolkit - Caballero, Alison; Leath, Katherine J.; Staton, Allie D. (Vaccines (Basel), 2023)
Widely accepted practices for the development of health education materials include the use of theoretically driven content, the execution of plain language writing and design strategies, the solicitation of community input, and a plan for dissemination via trusted messengers. Here, we describe the development of a COVID-19 vaccine education toolkit and share preliminary outcomes from dissemination via community health workers. The toolkit was developed to equip community messengers to educate community members about the COVID-19 vaccine. It includes an easy-to-read workbook for community learners, a Leader Guide with scripting, and additional resources for community health workers and other local messengers. The Health Belief Model was used to select content for the workbook, which was refined with input from community members. A team of trained plain language writers worked with clinicians and subject matter experts to draft content that was deemed readable, understandable, and actionable by formal measures and drafts were further refined with additional community feedback. Survey results from community health workers who used the toolkit to provide local education about COVID-19 vaccines indicate that the toolkit facilitated confidence in their ability to deliver scientific content to their community members. More than two-thirds report that use of the toolkit facilitated community members’ decisions to receive COVID-19 vaccines.